Deep Infiltrating Endometriosis Malignant Invasion of Cervical Wall and Rectal Wall With Lynch Syndrome： A Rare Case Report and Review of Literature - Li, Baoxuan; Wang, Yang; Wang, Yue; Li, Siman; Liu, Kuiran (Frontiers in Oncology, 2022)
Background Malignant transformation of deep infiltrating endometriosis (DIE) invading the cervix and rectum is quite rare, especially in patients combined with Lynch syndrome (LS). We report a rare case of a 49-year-old perimenopausal woman with endometrioid carcinoma arising from the pouch of Douglas, invading the cervix and rectum 1 year after a unilateral salpingo-oophorectomy treatment for ovarian endometriosis. The genetic testing of the patient showed germline mutations in MSH2, which combined with the special family history of colorectal cancer of the patient, was also thought to be associated with LS. We have analyzed the reported cases of DIE malignant transformation over the last 10 years, and reviewed the relevant literature, in order to strengthen the clinical management of patients with endometriosis, particularly patients with DIE, and reveal a possible correlation between malignant transformation of endometriosis and LS. Case Presentation A 49-year-old perimenopausal woman presented with hypogastralgia, diarrhea, and intermittent fever for more than 1 month. A Transvaginal ultrasound (TVS) showed a cervix isthmus mass, and a magnetic resonance imaging (MRI) showed a mass in pouch of Douglas with high suspicion of malignancy, possibly invading the anterior wall of the rectum. Prior to surgery, the patient performed the ultrasound guided pelvic mass biopsy through the vagina, and the pathology of the mass showed endometrioid carcinoma. The patient received a gynecological–surgical laparotomy and enterostomy, and a histopathology revealed endometrioid carcinoma infiltrating the cervical wall and rectal wall. In the family genetic history of the patient, her mother and two sisters suffered from colorectal cancer, so lesion tissue and blood were taken for genetic testing, which showed a germline mutation in MSH2, with LS being considered. After the surgical treatment, the patient received six courses of paclitaxel–carboplatin chemotherapy. During the course of treatment, bone marrow suppression occurred, but was healed after symptomatic treatment. To date, the patient is generally in good health, and imaging examination showed no evidence of recurrence. Conclusion The risk of malignant transformation of endometriosis is increased in perimenopause and postmenopause, as DIE is a rare malignant transformation of endometriosis. DIE can invade other adjacent organs and cause poor prognosis, thus, comprehensive gynecological–surgical treatment should be necessary. In addition, if histopathology showed endometrioid carcinoma, the possibility of LS should be considered, and if necessary, immunohistochemical staining and gene detection should be improved to provide follow-up targeted therapy and immunotherapy.